RISK FACTORS AND MENTAL HEALTH CHALLENGES ASSOCIATED WITH ALCOHOL CONSUMPTION AMONG UNDERGRADUATES IN LAGOS STATE - Blessing Oluwawole, Phebe; Abimbola Fadipe, Rasaq; Charles Kayode, Olajide; Chukwuewene Uwadia, John (African Journal of Social and Behavioural Sciences, 2026)
The high rate of alcohol consumption among undergraduates in Lagos State has become a serious concern, demanding urgent attention to safeguard undergraduates’ health and well-being. The study, therefore, examined the risk factors and mental health challenges associated with alcohol consumption among undergraduates in Lagos State, Nigeria. A descriptive survey design was employed in this study. A multi-stage sampling procedure was used to select 403 respondents from three universities in Lagos State. A research instrument, titled "Risk Factors and Mental Health Challenges of Alcohol Consumption Questionnaire (RFMHCACQ)" was used to collect data from the respondents. The content validity of the instrument was established by five experts from the Department of Social Work at the University of Ibadan, and the reliability was established using test re-test reliability method, which yielded a correlation coefficient of 0.88. The data collected were analysed using both descriptive and inferential statistics at the 0.05 level of significance. The findings revealed that academic pressure, emotional stress, and negative peer influence were among the major risk factors contributing to alcohol consumption. Findings further revealed that alcohol consumption has severe mental health consequences, such as cognitive impairment, obsessive-compulsive disorder, and social withdrawal. The findings showed no significant gender differences in either the risk factors for alcohol consumption or the associated mental health challenges. This concluded that both male and female undergraduates are equally vulnerable and require similar prevention and counselling interventions in school. It was therefore recommended that school counsellors should support undergraduates in managing academic pressure and emotional stress through regular exercise, time management workshops, and peer support groups to promote better mental health and reduce reliance on alcohol. Undergraduates should be encouraged by university counsellors and health practitioners to seek psychological interventions from counselling centres when experiencing mental health challenges related to alcohol consumption.